Dig4Life - DigComp in a serious game for high schools - Fiorese, Michela; Macrì, Angela; Deplano, Vindice (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The Serious Game (SG) is the concrete result of a highly structured Co-Design process, in the Eramsus + DIG4LIFE project, that involves teams of professors in 6 different countries. The SG created ad hoc for the project, offers to high school professors the opportunity to use an engaging tool with students that realizes a methodological approach in line with the educational needs of the new millennium and the specific need for digital maturity. The Serious Games give to educator, trainer, professor the opportunity to evaluate the level of knowledge, know-how and mindset in according with the subject / topic dealt with, and to train the digital skills. The SG become objects to think with and concretely opportunities for co-design and collaboration between students and teachers.